Property taxation and its revenue utilisation for urban infrastructure and services in Ghana: evidence from Sekondi-Takoradi metropolis. Issue 4 (15th August 2016) - Mabe, Joshua Biliwi; Kuusaana, Elias Danyi
Abstract : Purpose: This paper discusses property taxation and examines the extent of its contribution to financing urban infrastructure/services in Ghana. Dwelling on existing literature, it analyses the contribution of property tax to local level internally generated funds (IGF) and expenditure on urban infrastructure/services financed from IGF. Design/methodology/approach: Using a case study approach with a combination of both quantitative and qualitative research, this research was carried out in the Sekondi-Takoradi Metropolis in the Western Region, Ghana based on its economic and social diversity, business and economic opportunities and different land tenure systems. Data was collected through expert interviews and questionnaires, with a baseline study from 2006 to 2013. To check the veracity of data, triangulation of data was adopted. Findings: The study revealed that property rate accounted for 28% of IGF of the Sekondi-Takoradi Metropolitan Assembly (STMA). This revenue was expended mostly on waste management, education, social services, streetlights and health facilities. For the period between 2006 and 2013, property rates revenue alone was able to finance not less than 84% of total expenditure from IGF. It was estimated that if the challenges to property taxation were resolved in Ghana, the tax could finance the entire annual IGF budget of the STMA on urban infrastructure and services over and above the expended expenditure with a surplus margin of 13%. Practical implications: This paper makes available empirical evidence of property tax contribution to internally generated funds of STMA that could stimulate and enhance revenue mobilisation of other local government authorities. Debate on property tax revenue contribution towards financing urban infrastructure/services is also stimulated. Originality/value: There exist many researches on property tax however, none of these studies have examined the exact contributions of property rating revenue in financing urban infrastructure and services. This paper is the product of the original research conducted in Sekondi-Takoradi Metropolis.